Patients with antiphospholipid antibodies and venous thrombosis should receive long term anticoagulant treatment. - Derksen, R H (1993)
OBJECTIVE--To determine whether the finding of antiphospholipid antibodies in patients with venous thromboembolic episodes should influence the duration of treatment with anticoagulant drugs by mouth. METHODS--A retrospective study was carried out in 19 patients with antiphospholipid antibodies and a history of venous thromboembolic episodes. The median follow up from the first venous thromboembolic episode was 93 months and the median age at this episode was 26 years. The patients had in total 34 venous thromboembolic episodes. The total follow up period comprised 32 periods with and 23 periods without anticoagulant drugs. RESULTS--The probability of being free of recurrent venous thromboembolic episodes, calculated by the Kaplan-Meier method, was significantly influenced by the use of anticoagulant drugs. Patients receiving oral anticoagulants had at eight years a 100% probability of survival without recurrence, whereas patients in whom anticoagulant drugs were stopped had a 50% probability of a recurrent venous thromboembolic episode at two years, and a 78% probability of recurrence at eight years. CONCLUSION--Patients with venous thromboembolic episodes and antiphospholipid antibodies have a high risk for recurrent venous thromboembolic episodes and long term treatment with anticoagulant drugs by mouth is an effective prophylaxis.